Analysis of Christians Mental State in the Epidemic Period: Based on Ecclesiology, Sacrament, Eschatology - CUI, Renzhong (Journal of Research for Christianity in China (JRCC), 2023)
The COVID-19 pandemic is a severe test for people all over the world. From a macro perspective, it has deeply impacted various aspects of the world, including politics, economy, and culture. At the micro level, it has caused great emotional trauma to individuals. As a multi-ethnic and multi-religious country, different social communities have their own distinctive characteristics such as thinking and practice, and these different characteristics have been amplified to a certain extent in the context of the epidemic. Therefore, with the help of the combination of the background of the epidemic and the factors of the Christian community, this paper intends to briefly analyze the mental state of Christians during the epidemic period with the Ecclesiastical dimension, Sacramental dimension and Eschatological dimension of Christian theology, so as to open up a new perspective for understanding the unique thinking characteristics of this community.